Association of PCSK1 rs6234 with obesity and related traits in a Chinese Han population. - Qibin Qi; Huaixing Li; Ruth J F Loos; Chen Liu; Frank B Hu; Hongyu Wu; Zhijie Yu; Xu Lin (PLoS ONE)
Background Common variants in PCSK1 have been reported to be associated with obesity in populations of European origin. We aimed to replicate this association in Chinese. Methodology/principal findings Two PCSK1 variants rs6234 and rs6235 (in strong LD with each other, r(2) = 0.98) were genotyped in a population-based cohort of 3,210 Chinese Hans. The rs6234 was used for further association analyses with obesity and related traits. We found no significant association of rs6234 with obesity, overweight, BMI, waist circumference, or body fat percentage (P > 0.05) in all participants. However, the rs6234 G-allele showed a significant association with increased risk of combined phenotype of obesity and overweight (OR 1.21[1.03-1.43], P = 0.0193) and a trend toward association with obesity (OR 1.25[0.98-1.61], P = 0.08) in men, but not in women (P > or = 0.29). Consistently, the rs6234 G-allele showed significant association with increased BMI (P = 0.0043), waist circumference (P = 0.008) and body fat percentage (P = 0.0131) only in men, not in women (P > or = 0.24). Interestingly, the rs6234 G-allele was significantly associated with increased HOMA-B (P = 0.0059) and decreased HOMA-S (P = 0.0349) in all participants. Conclusion/significance In this study, we found modest evidence for association of the PCSK1 rs6234 with BMI and overweight in men only but not in women, which suggested that PCSK1 rs6234 might not be an important contributor to obesity in Chinese Hans. However, further studies with larger sample sizes are needed to draw a firm conclusion.